Uji Performa Mesin Penggiling Padi dengan Rice Rubber Roller Horizontal: Performance Test of a Rice Milling Machine with a Horizontal Rice Rubber Roller - Suwandi, Dedi; Badruzzaman, Badruzzaman; Amat, Mohammad Azwar; Luthfi, Muhammad (Journal of Applied Mechanical Technology, 2024)
Huller is the main machine that determines the quality and quantity of production in the rice milling industry. The current problem, especially in the small-scale rice milling industry, is that they still use locally made huller machines that use 6-inch diameter rice rubber rollers with a capacity of 800-1,200 kg/hour. Local huller machines produce a yield (broken rice) of 30-40%, so three huller machines and one polisher machine are needed in one production line. This machine assembly requires energy, human power and high costs. With these problems, a machine is needed that is capable of increasing the yield and milling capacity. Huller machine with horizontal rice rubber roller has a dimension specification of 1.3X0.9X2 meters; Rice rubber roller diameter 10 inches; 3 phase electric motor 20HP 15KW 1,500 rpm. The huller machine has been tested at the CV. Putra Maju rice mill, Wirakanan Village, Kandanghaur District, Indramayu Regency for 4 months. Test results Huller machine capacity 1,600 kg/hour ± 50 kg with a yield of 72% ± 2%.